2019
DOI: 10.18097/pbmc20196501063
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of prostacyclin synthase with cytochromes P450

Abstract: Biosensor experiments on investigation of interaction between prostacyclin synthase (PGIS) and different proteins of the cytochrome P450 monooxygenase systems were perfomed. Interaction of PGIS with microsomal (CYP21A2, CYP2E1) and mitochondrial (CYP27A1, CYP11B1, CYP11B2, CYP11A1) cytochrome P450s was detected. Kinetic and equilibrium parameters of protein complexes formation were determined. Data obtained suggest an essential role of these hemoproteins interaction in regulation of prostacyclin and thromb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…CYB5D2 is a member of the progesterone membrane receptor-associated family and relies on the binding of heme to its cytochrome b5-like heme/steroid domain to exert biological activity ( 19 ). It is well known that CYB5D2 expression is downregulated in diverse cancers and act as tumor suppressors ( 8 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…CYB5D2 is a member of the progesterone membrane receptor-associated family and relies on the binding of heme to its cytochrome b5-like heme/steroid domain to exert biological activity ( 19 ). It is well known that CYB5D2 expression is downregulated in diverse cancers and act as tumor suppressors ( 8 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, surface plasmon resonance-based biosensors are widely used to study various interactions, including 1) protein-protein interaction [106,107]; 2) antigen-antibody interaction [108]; 3) protein-lipid interaction [109,110]; 4) low-molecular-weight ligand-protein interaction [111,112]; and 5) the influence of low-molecular-weight compounds on protein-protein interactions [113,114].…”
Section: Analysis Of the Interaction Of The Viral Antigen (D Antigen)...mentioning
confidence: 99%
“…In previous publications, it was shown that both thromboxane and prostacyclin synthases had formed stable molecular complexes with a number of protein partners (Ershov et al, 2019a; Gnedenko et al, 2019; Svirid et al, 2017). Taken together, the SPR‐validated PPIs are shown schematically in Figure 1.…”
Section: Binary Ppis Involving Cyp5a1 and Cyp8a1mentioning
confidence: 99%
“…The phenomena of CYP/CYP hetero‐oligomerization is featured and well‐studied for many members of the cytochrome P450 superfamily, and it is believed to be associated with the modulating effect on the enzymatic reaction parameters of interacting cytochrome P450s (Bostick et al, 2016; Hazai & Kupfer, 2005; Reed & Backes, 2012). Hence, the complex formation between CYP5A1 (or CYP8A1) and microsomal CYPs (Gnedenko et al, 2019; Svirid et al, 2017) is obviously a particular case of CYP/CYP interactions described in the literature. Although it has been yet impossible to investigate the functional consequences of CYP5A1/CYP and CYP8A1/CYP hetero‐complexes, we can assume that such a modulation exists.…”
Section: Binary Ppis Involving Cyp5a1 and Cyp8a1mentioning
confidence: 99%
See 1 more Smart Citation